EVALUASI SUMATIF PROGRAM PENDIDIKAN DALAM PERSPEKTIF MODEL CIPP (Context, Input, Process, Product) DI UPTD SD NEGERI 2 PANDAN SARI - Yuliani, Rika; Hidayah, Nurul; Suhaimi; Sulistiyana (Information Technology Education Department, 2026)
Summative evaluation of educational programs is an essential instrument to ensure school quality and accountability. This study was conducted at UPTD SD Negeri 2 Pandan Sari with the aim of analyzing the effectiveness of its educational program through the lens of the CIPP model (Context, Input, Process, Product). The research employed a qualitative approach, utilizing interviews, observations, and documentation as data collection techniques. The participants included the principal, teachers, and educational staff. The findings indicate that: (1) in terms of context, the program was designed in alignment with the school’s vision and mission; (2) in terms of input, human resources, facilities, and infrastructure adequately supported program implementation; (3) in terms of process, activities were carried out consistently, although documentation practices require improvement; and (4) in terms of product, the program had a positive impact on students’ literacy development, character formation, social skills, and academic achievement. The study concludes that the CIPP model provides a comprehensive evaluation framework and offers a holistic overview of program effectiveness. These findings serve as a foundation for schools to formulate continuous improvement strategies aimed at enhancing educational quality. Keywords: Summative Evaluation; CIPP Model; Educational Program; Elementary School.